Software-Defined Networking (Sdn) In Modern Network Management - Rahma Fitria; Desvina Yulisda; Sayed Fachrurrazi (Universitas Malikussaleh, 2021)
Modern computer network implements tasks from routing, monitoring traffic, accessing control and balancing server load. Software-Defined Networking (SDN) has become a new radical model where the network is programmable. The network can be simplified and managed through network programmability. In addition, SDN offers a very good interface between networking devices and the software that control this activity. This paper presents the SDN architecture, ForCES, and OpenFlow protocol to allocate information exchange. Oracle and HP is presented as an organization that built SDN product by having different architecture. Always as a new solution for computer network has been proposed, it still has challenges for researcher to solve the SDN issues that has been raised. Keywords: Software-Defined Networking (SDN), programmable networks, ForCES, OpenFlow